Internet of Things and its use in a corporate environment - Hausteinová, Iveta (2017)
This thesis focuses on phenomenon of the Internet of Things. It consists of 4 chapters. First chapter is focused on the introduction of IoT and the technolohies that are used within this concept. Next chapter is about IoT in the Czech Republic and application cases.